Sensitivitätsanalyse klimabezogener Transitionsrisiken des deutschen Finanzsektors; Sensitivity analysis of climate-related transition risks in the German financial sector - Dominik Schober; Tobias Etzel; Alexander Falter; Ivan Frankovic; Christian Gross; Anke Kablau; Pierre Lauscher; Jana Ohls; Lena Strobel; Hannes Wilke (Deutsche Bundesbank, 2021)
Klimabezogene Risiken aus der Transition zu einem CO2-armen Wirtschaftssystem können potentielle Verwundbarkeiten des Finanzsystems offenlegen. Wir entwickeln und beschreiben in diesem Artikel ein Instrumentarium zur Analyse dieser Risiken und wenden es auf das deutsche Finanzsystem an. Die Verwendung langfristiger, konsistenter Klimaszenarien, die im Rahmen der gemeinsamen Arbeiten des Network for Greening the Financial System (NGFS) entstanden sind, erlauben die Modellierung der Auswirkungen der Transition und die anschließende Abbildung in das Finanzsystem. Wir nutzen eine umfassende Datenbasis hinsichtlich der einbezogenen Finanzintermediäre und -instrumente und zeigen, dass sich die potentiellen Portfolioverluste aus einem unerwarteten Klimapolitikwechsel im Aggregat für die einzelnen Finanzsektoren im geringen bis mittleren einstelligen Prozentbereich bewegen. Einzelne Finanzintermediäre sind dabei stärker von Transitionsrisiken betroffen. Die Unsicherheit über die aktuellen Erwartungen der Marktakteure führt zu Ergebnissen, welche von den abgeleiteten potentiellen Portfolioverlusten um bis zu 40 % abweichen können. – – Climate-related risks arising from the transition to a low-carbon economy may expose potential vulnerabilities in the financial system. In this article, we develop and describe a set of tools for analysing these risks and apply them to the German financial system. The use of longterm, consistent climate scenarios that have been developed as part of the joint work of the Network for Greening the Financial System (NGFS) allows the effects of the transition to be modelled and then mapped to the financial system. We use a comprehensive dataset in terms of the financial intermediaries and financial instruments reviewed, and demonstrate that the aggregated potential portfolio losses from an unexpected change in climate policy are within the low to medium single-digit percentage range for individual financial sectors. Individual financial intermediaries are more severely affected by transition risks. Uncertainty about the current expectations of market participants leads to results that may deviate by up to 40% from the potential portfolio losses calculated.
Keywords: D53; E27; H23; Q51; Q54; 330; climate scenarios; climate transition risks; macroeconomic and financial impacts; financial stability analysis; sensitivity test; carbon pricing